Epidemiology, Social Sciences and Syndemic - Murguía Lores, Adriana (Espacio Abierto, 2021)
After the first months of the pandemic, data and reflections concerning the relation between unequal social conditions and higher risks of contracting and dying from COVID-19 emerged. The sanitary emergence has deepened the positive relation between health inequalities and adverse social conditions that has been documented since the nineteenth century. This reflection traverses the ways in which this problem has been addressed by epidemiology and social epidemiology, emphasizing the disciplinary intersections between the latter and the social sciences, illustrating how the phenomena produced by the pandemic have been addressed by these theoretical frameworks. It also addresses the consideration of the current situation as a syndemic, and the theory of fundamental causes as a conceptual framework that enables the empirical analysis of one of the many levels involved in the observed phenomena.